2020
DOI: 10.2147/opth.s256891
|View full text |Cite
|
Sign up to set email alerts
|

<p>Overnight Safety Evaluation of a Multi-Pressure Dial in Eyes with Glaucoma: Prospective, Open-Label, Randomized Study</p>

Abstract: Purpose: To investigate the safety and tolerability of the multi-pressure dial (MPD) worn overnight for seven consecutive days. Design: Prospective, open-label, randomized, single-site study. Subjects: Twenty eyes of 10 subjects with open-angle glaucoma were fitted with an MPD and randomized to negative pressure application of −10 mmHg in one eye (study eye) worn overnight for 7 consecutive days. Methods: Safety measures included best-corrected visual acuity (BCVA), intraocular pressure (IOP) changes from base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 23 publications
9
15
0
Order By: Relevance
“…Further, there was no evidence of rebound IOP spikes following the application of negative pressure across all test runs. The results of this study confirm that controlled application of periocular negative pressure leads to a reduction in IOP, supporting the results of prior clinical studies [6,7,10] that reported a reduction in IOP with the MPD system. Collectively, Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Further, there was no evidence of rebound IOP spikes following the application of negative pressure across all test runs. The results of this study confirm that controlled application of periocular negative pressure leads to a reduction in IOP, supporting the results of prior clinical studies [6,7,10] that reported a reduction in IOP with the MPD system. Collectively, Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Given that the changes in RBP fell below the range of uncertainty in both subjects, we concluded there was no detectable change in RBP with application of negative pressure across all test runs. Multiple prior studies have investigated the IOP-lowering ability of the MPD in both healthy and glaucomatous eyes as measured via the excursion test method, a developed technique for IOP measurement that involves a pneumatonometer across a tonometer tip cover (Tono-penÒ; Reichert Technologies, Buffalo, New York) with a specially adapted version of the MPD goggles [6,7,10]. In a recent study in 65 healthy subjects, Swan et al [6] used three different negative pressure settings, namely 25, 50 and 75% of baseline IOP, and demonstrated a stepwise increase in IOP reduction with increased levels of negative pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, an IOP reduction was also observed in the contralateral, or control eye. Although a minor reduction, this has not been demonstrated in prior studies evaluating the IOP-lowering ability of the device [22,24] and suggests future investigation is warranted evaluating the IOP-lowering ability of the MPD in the nocturnal setting and/or supine position.…”
Section: Discussionmentioning
confidence: 81%
“…A prior study investigating the safety and tolerability of continuous, nightly wear of the MPD over a 7-day period [22] produced favorable results, indicating that patients would be amenable to continuous overnight wear. This earlier study primarily focused on the safety and tolerability of the MPD and did not obtain IOP measurements in the nocturnal setting or supine position.…”
Section: Discussionmentioning
confidence: 99%
“…The MPD, a novel device currently under investigation, decreases IOP by modulation of atmospheric pressure in a localized, enclosed microenvironment immediately anterior and external to the patient’s eye. With prior work 10 , 13 establishing the IOP-lowering benefit of the device with direct application of negative pressure (e.g. patient awake with eyelids open) to the cornea, this study aimed to investigate with a model whether a mitigation in negative pressure application occurs when applied through tissue (e.g.…”
Section: Discussionmentioning
confidence: 99%